Hybrid TOA/AOA techniques for mobile location in non-line-of-sight environments - Venkatraman, S.; Caffery, J. (2004 IEEE Wireless Communications and Networking Conference, 2004)
Techniques for locating wireless subscribers for E-911 emergency services must meet the stringent accuracy requirements set by the FCC. In non-line-of-sight propagation conditions, large measurement errors with unknown statistics cause standard location schemes to perform poorly. In these challenging environments, it is necessary to develop methods that can integrate heterogeneous measurements and utilize all available information to mitigate the errors and improve location accuracy. This paper illustrates a hybrid time and angle of arrival technique that utilizes non-linear constrained optimization to estimate the mobile terminal's location with bounds on the range and angle errors inferred from geometry. Another simple hybrid TOA/AOA algorithm based on a least squares solution of lines of position is also proposed. These algorithms are compared to previous approaches using TOA only and simulation results are provided that show the accuracy gains of the proposed algorithms.